2016
DOI: 10.1007/s10067-016-3226-9
|View full text |Cite
|
Sign up to set email alerts
|

Is ankle involvement underestimated in rheumatoid arthritis? Results of a multicenter ultrasound study

Abstract: The aim of this study is to investigate the prevalence of subclinical ankle involvement by ultrasound in patients with rheumatoid arthritis (RA). The study was conducted on 216 patients with RA and 200 healthy sex- and age-matched controls. Patients with no history or clinical evidence of ankle involvement underwent US examination. For each ankle, tibio-talar (TT) joint, tibialis anterior (TA) tendon, extensor halux (EH) and extensor common (EC) tendons, tibialis posterior (TP) tendon, flexor common (FC) tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
7
12
1
1
Order By: Relevance
“…No PD positivity was found on plantar flexors. Ankle involvement in RA seems to also be underestimated-in a previous study, ankle abnormalities were found in >80% of RA active patients [37]. No PDUS ankle pathology was found in our cohort of patients.…”
Section: Discussioncontrasting
confidence: 47%
“…No PD positivity was found on plantar flexors. Ankle involvement in RA seems to also be underestimated-in a previous study, ankle abnormalities were found in >80% of RA active patients [37]. No PDUS ankle pathology was found in our cohort of patients.…”
Section: Discussioncontrasting
confidence: 47%
“…Gutierez et al [45] in a study on patients with RA and subclinical ankle involvement (asymptomatic patients without history or clinical evidence of ankle injury), identified US abnormalities at the level of the ankle in 87% of the patients, significantly more than in healthy individuals. The most frequently reported was tibialis posterior tenosynovitis (31.9% of patients), followed by peroneus longus tenosynovitis and TT synovitis (26.9% and 25% of patients, respectively), but they did not find a significant association between the US abnormalities and disease duration or disease activity.…”
Section: Ultrasound Findings Of the Anklementioning
confidence: 99%
“…Each tendon and joint were assessed in both longitudinal and transverse planes. The total number of erosions were examined at 100 location sites (minimum) of each patient as described in Table . The setting of gray‐scale/power Doppler was 17 MHz frequency of B‐mode, 6.25 MHz frequency of power Doppler, and 610 MHz frequency of Power Doppler pulse repetition.…”
Section: Methodsmentioning
confidence: 99%